Pengaruh Prediksi Kebangkrutan Dengan Model Altman Z-Score dan Fulmer H-Score Terhadap Harga Saham Badan Usaha Milik Negara Non-Perbankan yang Terdaftar di Bursa Efek Indonesia - Gusti Ayu Mita Dwi Lestari; I Gede Agus Pertama Yudantara (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of bankruptcy prediction by the Altman Z-Score and Fulmer H-Score models on the stock price of Non-Banking State-Owned Enterprises listed on the Indonesia Stock Exchange. The sample of this study was selected using a purposive sampling technique and consisted of 15 Non-Banking State-Owned Companies listed on the Indonesia Stock Exchange. This study used secondary data derived from the company's financial statements and stock summaries for the 2015-2020 period. The research method used is descriptive quantitative. The analysis technique of this research was statistics using the SPSS application. The results show that partially, bankruptcy prediction using the Altman Z-Score and Fulmer H-Score models has a significant positive effect on stock prices, so both models can be used to estimate future stock price changes. The results also show that bankruptcy prediction using both models simultaneously affects the stock prices.